Effect of laser irradiation of the thymus projection on the level of cytokines in mice tissues - Kanevsky, V.А.; Pushkarev, V.M. (Reports of the National Academy of Sciences of Ukraine, 2016)
The low-intensity femtosecond multichannel laser action upon the levels of cytokines in blood, skin, and thymus of irradiated mice with emphasis on cytokines and chemokines that determine the growth, proliferation, and differentiation of blood cells is studied. At a high intensity irradiation (20 mW/cm2), the content of IL-3, IL-5, Eotaxin, G-CSF, GM-CSF, and KC significantly increases in thymus. It is assumed that this is due to the cell maturation reorganization in gland after the laser irradiation.